The Influence of GHRM and Organizational Culture on Environmentally Friendly Companies - Wahyuni, Eka; Waskito, Jati (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The purpose of this study is to analyze the role of organizational commitment as mediating the influence of GHRM & organizational culture on Eco Friendly at Dishub Boyolali. This research method is quantitative. The population in the study were employees of the Boyolali Regency Transportation Office. In sampling this study using non-probability sampling method with purposive sampling. The number of samples of this study were 100 respondents. The data analysis method uses SMART PLS. The results of this study are that GHRM has a negative and insignificant effect on Eco-Friendly at the Boyolali Transportation Office. Organizational Culture has a positive and significant effect on ECO Friendly at the Boyolali Transportation Agency. GHRM has a positive and significant effect on organizational commitment at the Boyolali Transportation Agency. Organizational culture has a positive and significant effect on organizational commitment at the Boyolali Transportation Agency. Organizational commitment has a negative and insignificant effect on mediating the effect of GHRM on eco-friendly. Organizational commitment mediates organizational culture on eco-friendly negatively and insignificantly.